Monetary policy dynamics impact on foreign direct investment in Malaysia - Leong, Kai Wen; Tan, Chiaw Yee; Tan, Hui Xian; Wong, Shi Hui (2024)
The objective of this project is to explore the monetary policy dynamics impact on foreign direct investment (FDI) in Malaysia. Five independent variables are employed in this project. The independent variables are real interest rate (RIR), foreign exchange rate (FER), taxation (TAX), trade openness (TO), and unemployment (UNEMP). Five of the independent variables are all crucial to examine the attractiveness level of foreign direct investment inflow in Malaysia. Time series analysis is utilized in this research and the data collection involved 30 years, from 1993 to 2022. Based on the data collected, the ARDL model is performed using Eviews. The ARDL explained the long run impact on the five independent variables towards foreign direct investment inflows in Malaysia. The regression model has been proven to be to be stationary through the unit root test. By conducting the Breusch-Godfrey serial correlation LM test, ARCH test, CUSUM and CUSUMSQ test, the model is confirmed to exclude autocorrelation, heteroscedasticity and unstable issues. The results of this research demonstrated that different factors bring different impact in attracting foreign direct investment. Real interest rate, foreign exchange rate and trade openness explained a negative correlation on the foreign direct investment. In brief, the findings and discussions of this project can act as a reference for investors, companies, policy makers and future researchers to gain valuable insights